Heart’s secret encounter-extra skeletal Ewings sarcoma with cardiac involvement in adult: a case report - Thomas, Arppana; Salahuddin, Sameer; Rajendran, Deepu; Legha, R.; Praseeda,; Thomas, Chandni (International Journal of Research in Medical Sciences, 2025)
Ewing sarcoma is a rare, aggressive malignant tumour predominantly arising from bone or soft tissue in adolescents and young adults. Primary cardiac involvement is exceedingly uncommon, usually occurring as a result of metastatic spread. Here, we present a case of 22-year-old male with an atypical primary cardiac presentation of Ewings sarcoma, posing significant diagnostic challenges. A detailed evaluation revealed disseminated malignancy, including cardiac and systemic involvement. This report underscores the importance of rare malignancies in atypical cardiac presentations and highlights the value of a multidisciplinary approach in diagnosis and treatment.